An Overview on Carbon Quantum Dots Optical and Chemical Features - Marco Giuseppe Giordano; Giulia Seganti; Mattia Bartoli; Alberto Tagliaferro (Molecules, 2023)
Carbon quantum dots are the materials of a new era with astonishing properties such as high photoluminescence, chemical tuneability and high biocompatibility. Since their discovery, carbon quantum dots have been described as nanometric high-fluorescent carbon nanoparticles, but this definition has become weaker year after year. Nowadays, the classification and the physical explanation of carbon quantum dots optical properties and their chemical structure remain matter of debate. In this review, we provide a clear discussion on these points, providing a starting point for the rationalization of their classification and a comprehensive view on the optical and chemical features of carbon quantum dots.